INSTITUTIONAL MULTILINGUALISM IN THE EUROPEAN UNION – POLICY, RULES AND PRACTICE - PALUSZEK, Karolina (Comparative Legilinguistics, 2015)
This paper examines the rules and working practices of main institutions of European Union in relation to EU policy multilingualism. The institutions analysed in this research include the Commission, the Council of the European Union, the Court of Justice of the European Union, and the European Parliament. After presenting the legal basis of EU multilingualism, the study identifies the achievements and difficulties met by EU institutions in the process of its realisation. Topic highlighted in this study include: Problems resulting from the status and number of official EU languages. The distinction made between EU institutions obliged to observe citizens’ language rights and other bodies that can seemingly make their own rules. Inconsistencies between the practice of internal and external communication of the EU institutions, presenting examples from individual institutions, as well as from judicial practice of the Court of Justice of the European Union. Finally, the article presents an evaluation of the solutions to the observed problems presented in the literature, along with the author’s own conclusions.